Supplemental Bacillus subtilis DSM 32315 manipulates intestinal structure and microbial composition in broiler chickens - Ma, Youbiao; Wang, Weiwei; Zhang, Haijun; Wang, Jing; Zhang, Wenming; Gao, Jun; Wu, Shugeng; Qi, Guanghai (Scientific reports, 2018)
Knowledge about the modulation of gut microbiota improves our understanding of the underlying mechanism by which probiotic treatment benefits the chickens. This study examined the effects of Bacillus subtilis DSM 32315 on intestinal structure and microbial composition in broilers. Broiler chicks were fed basal diets without or with B . subtilis supplementation (1.0 × 10 9 spores/kg of diet). Supplemental B . subtilis increased average body weight and average daily gain, as well as elevated villus height and villus height to crypt depth ratio of ileum in broilers. Multi-dimension analysis showed a certain degree of separation between the cecal microbiota from treatment and control groups. Increased Firmicutes abundance and reduced Bacteroidetes abundance in cecum were observed responded to B . subtilis addition, which also increased the abundances of Christensenellaceae and Caulobacteraceae , and simultaneously decreased the abundances of potentially harmful bacteria such as Vampirovibrio , Escherichia/Shigella and Parabacteroides . Network analysis signified that B . subtilis addition improved the interaction pattern within cecal microbiota of broilers, however, it exerted little influence on the metabolic pathways of cecal microbiota by comparison of the functional prediction of metagenomes. In conclusion, supplemental B . subtilis DSM 32315 improved growth performance and intestinal structure of broilers, which could be at least partially responsible by the manipulation of cecal microbial composition.